Faktor – Faktor Yang Berhubungan Dengan Pemilihan Alat Kontrasepsi Suntik Pada Wanita Usia Subur (WUS) Di Praktek Bidan Mandiri Efita P.S Tahun 2022 - Sardevi Sardevi; Ninsah Mandala Putri Br Sembiring (Jurnal Sains dan Kesehatan, 2022)
Family planning is an active concern for the role of the community by delaying the age of marriage, controlling the number of children, and increasing family welfare in order to realize a happy and prosperous small family. This study aims to determine the factors related to the choice of injecting contraceptive methods for women of childbearing age at the independent midwife practice Elfita P.S in 2022. This type of research is an analytic survey with a cross-sectional approach. The number of samples used was 36 people. The data analysis technique uses the Chi Square test. the results obtained from 36 respondents, there is a relationship of knowledge in the choice of injection contraception by women of childbearing age, the p value is 0.0219 <0.05. there is a relationship between age in the choice of injection contraception by women of childbearing age, the p value is 0.047 <0.05. there is a relationship between education in the choice of injection contraception by women of childbearing age, the p value is 0.0240 <0.05.